Apocalypse Deferred : Girard and Japan - Alberg, Jeremiah, 1957- (Book collections on Project MUSE., 2017)
The essays in Part I of Apocalypse Deferred are primarily rooted in the events of World War II. The contributors employ mimetic theory to respond to the use of nuclear weapons and the threat of absolute destruction. Essays in Part II cover a wide range of topics in Japanese cultural history from the viewpoint of mimetic theory, ranging from classic and modern Japanese literature to anime. Essays in Part III address theological questions and mimetic theory, especially from a Judeo-Christian perspective.